Training Workshop for NARES and Private Sector on GapFinder: Monitoring Farmer Adoption of Sustainable Rice Practices - Suh, Neville; Ahouanton, Kokou; Dossou-Yovo, Elliott (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
Promoting sustainable rice production is a critical priority for developing countries like Mali, where rice serves as a key staple food. In Mali, the AICCRA project seeks to advance sustainable rice farming by building farmers' skills and capacities in adopting a range of climate-smart best management practices. Although 81,146 farmers (including 37,249 women) have been exposed to various climate-smart technologies—such as mechanization services, drought-tolerant rice varieties, and RiceAdvice—it remains uncertain to what extent these practices are being effectively implemented or whether farmers face obstacles limiting their full adoption. To address this, AICCRA organized training for the National Agricultural Research and Extension Services (NARES), private sector stakeholders, and lead farmers in Mali on the use of Rice GAPfinder, a tool designed to benchmark farmers' practices and track their progress toward sustainable rice production. The training involved evaluating key performance indicators (PIs) to identify priority areas for targeted capacity building. A two-day workshop held in the Sikasso region trained 13 participants on how to use Rice GAPfinder to assess farmers’ sustainable rice production practices. Participants were trained on 12 performance indicators, including profitability, labor productivity, yield productivity, water productivity and quality, nitrogen-use efficiency, phosphorus-use efficiency, biodiversity, greenhouse gas emissions, food safety, health and safety, child labor and youth inclusion, and women’s empowerment. The outcomes of this activity will provide insights into farmers’ adoption of sustainable rice practices and highlight areas for further improvement and capacity-building efforts. The ultimate goal is to enhance the adoption of sustainable practices that improve resource use efficiency, reduce the environmental and climate impacts of rice farming, and increase productivity.